Cutting red tape for trade in services - Milena Kern; Jörg Pätzold; Hannes Winner (Austrian Institute of Economic Research (WIFO), 2019)
Trade in services is often hampered by domestic administrative barriers, even when countries are members of the same regional trade agreement. We exploit a large reform in the European Union (the EU Service Directive) aimed at reducing such administrative hurdles in cross-border service provision to estimate its effects on service trade. We employ a difference-in-difference strategy and a Pseudo Poisson Maximum Likelihood (PPML) panel approach to estimate gravity equations with multiple fixed effects. On average, the reform increased intra-EU trade in targeted services between a lower bound of 27 percent and an upper bound of 55 percent, translating into an overall welfare increase between 0.35 and 1.04 percent. This effect of the reform on service trade is corroborated by several robustness and placebo checks. Finally, a disaggregated analysis reveals significant differences between countries and service sectors.
Keywords: F13; F14; F15; 330; Service trade; trade liberalisation; gravity equation; European integration